KEBIJAKAN PENGURANGAN PAJAK PBB-P2 DI KOTA TANGERANG SELATAN: KEWENANGAN PEMERINTAH DAN UNDANG-UNDANG NOMOR 1 TAHUN 2022: PBB-P2 Tax Reduction Policy in South Tangerang: Government Authority and Law No. 1 Year 2022 - Elsya Dana Yuana Amos; Ignatius Pradipa Probondaru (Reformasi Hukum Trisakti, 2025)
South Tangerang City Government in the Rural and Urban Land and Building Tax (PBB-P2) Reduction Policy for 2022-2023, South Tangerang City Government provided incentives in the form of reductions in the principal amount of tax and the elimination of administrative sanctions. This policy was adopted following the enactment of Law Number 1 of 2022, which grants greater authority to local governments in managing their revenue sources, including PBB-P2. The legal issue addressed in this research is how the regulation and impact of the PBB-P2 reduction policy affects local revenue and taxpayer compliance. The legal research method employed is normative legal research, using a descriptive approach through the analysis of secondary data to assess the policy’s compliance with national statutory provisions. Based on the findings of the analysis, it is concluded that although this policy may potentially reduce local revenue, it generally enhances taxpayer awareness and compliance while supporting public welfare. This research is expected to provide strategic recommendations to optimize local tax policies in promoting regional economic growth.